Katrina, Wilma and Me: Learning to Live with Climate Surprises? - Grimm, Kurt (Geoscience Canada, 2006)
SUMMARY High-stakes and large uncertainties characterize the science, policy and reality of climate change. A simple analysis of what appears to be most likely for the immediate future of Earth's climate system, including some probable human vulnerabilities, is presented below. In short, climate change is real. Further, numerous observations suggest the onset of a rapid phase transition between the familiar Holocene climatic mode and some future quasi-stable steady state. Such a climatic phase transition may extend from years to decades, presenting dramatic and unfamiliar challenges to ecological and societal organizations at all scales. Potential human hazards – particularly grave for food production – may catalyze dramatic societal changes. The profound uncertainty of abrupt climate change warrants careful reflection and prudent preparation, including assessment and enhancement of household, local and bioregional adaptive capacities.